Strategi Pembuatan Video Konten Digital Marketing Melalui Aplikasi Tiktok Di SMK N 1 Semarang - Nova Amalia Fitri; Luluk Nayang; Alvin Surya Close; Virma Irmanda; Nurizka Alledya Zakina; Desti Arbaeti Hidayah; Salma Atika; Suhariyanto Suhariyanto (STIKes Ibnu Sina Ajibarang, 2024)
Modern technological advances cannot be separated from society, and significant developments in the use of digital devices have changed the media environment. Social media is now used for various purposes, including interaction, information, news and entertainment. Platforms like TikTok have become the main tool in digital marketing in Indonesia. TikTok offers creative short video formats, advanced algorithms, and features like “Hashtag Challenges” and “Branded Effects” that attract brands and companies. Students at SMK Negeri 1 Semarang face challenges in attracting an audience on TikTok due to lack of market research, creativity, and limited resources. This service aims to improve the understanding and skills of SMK N 1 Semarang students in creating quality video content on TikTok. The participatory method used involves discussion and direct practice. The evaluation results showed a significant increase in students' understanding of video content creation, with 55.8% of participants understanding the material presented. This education is expected to increase students' competence and creativity in digital marketing using TikTok.